SPHK Inhibitors and Zoledronic Acid Suppress Osteoclastogenesis and Wear Particle-Induced Osteolysis - Gu, Minghui; Pan, Baiqi; Chen, Weishen; Xu, Hai; Wu, Xiaoyu; Hu, Xuantao; Zheng, Linli; Ye, Yongyu; Meng, Qing; Xian, Guoyan; Zhang, Ziji; Sheng, Puyi (Frontiers in Pharmacology, 2022)
Background: Inflammatory osteolysis induced by wear particles is the major cause of prosthetic loosening after artificial joint replacement, and its prevention and treatment are difficult worldwide. Our previous study confirmed that sphingosine kinases (SPHKs) are important mediators regulating the wear particle-induced macrophage inflammatory response. However, it is unclear whether SPHKs can modulate chronic inflammation and alleviate osteolysis. Zoledronic acid (ZA), an imidazole-containing bisphosphonate, directly affects osteoclasts and prevents bone mineral-related diseases. However, the effects of SPHK inhibitors and ZA used to treat periprosthetic osteolysis are unknown. Methods: We applied Tartrate-resistant acid phosphatase (TRAP) staining to evaluate bone destruction in the interface membranes of patients with aseptic loosening and a control group. A murine calvarial osteolysis model was used to examine the preventative effect of SPHK inhibitors and ZA on osteolysis. Micro-CT scanning, immunohistochemistry (IHC), and histomorphometric analysis were conducted to determine the variations in inflammatory osteolysis. The effects of different drug concentrations on cell viability were evaluated using the cell counting kit-8 (CCK-8) assay. Real time quantitative polymerase chain reaction (RT-qPCR) analysis was performed to confirm the reduced expression of osteoclast-specific genes after drug and titanium treatment. The osteoclast formation and functions of the drugs were analyzed using TRAP staining in vivo and in vitro. The effect of SPHKs/S1P-TRAF2-BECN1 signaling pathways was verified via the RT-qPCR and tissue IHC. Results: In this study, we found that SPHK inhibitors (ABC294640 and FTY720) combined with ZA decreased the degree of inflammatory osteolysis in vivo. However, ABC294640 and ZA suppressed osteoclast differentiation and osteoclast-specific genes in vitro. SPHKs regulate the inflammatory osteolysis induced by wear particles by increasing the expression of SPHKs/S1P-TRAF2-BECN1. Conclusions: Our study revealed that SPHKs could initiate osteolysis induced by wear particles. Moreover, SPHK inhibitors combined with ZA inhibit osteoclast genesis through SPHKs/S1P-TRAF2-BECN1, suggesting that SPHK inhibitors and ZA provide a new perspective and scientific basis for the prevention and treatment of prosthesis loosening.